Obesitas sebagai Faktor Risiko Terjadinya Premenstrual Syndrome pada Mahasiswa Akademi Kebidanan Pemerintah Kabupaten Kudus - Magdalena Dyah Puspitorini, Mohammad Hakimi, Ova Emilia (Fakultas Kedokteran Universitas Gadjah Mada, 2007)
Background: Emotional changes and physical disorders at premenstrual period are common among reproductive- age females. The problem might lead to decrease inworking productivity and ininterpersonal problems. Obese females (BMI> 30) are at higher risk of experiencing premenstrual syndromes. A preliminary study at Midwifery Academy in Kudus District had revealed the overweight and obesity prevalence of 13.72% and 11.87%. The figures were higher than the predicted obesity prevalence of 4.7% in the year 2000.Aim: The study was conducted to identify the relationship between body mass index and premenstrual syndrome.Methods: Cross sectional research was conducted to collect data from 371 students from Midwifery Academy in Kudus District. Univariate analysis was used to describe the frequency distribution. Bivariate analysis using chi-square for trend and chi square tests, as well as multivariate analysis with applied logistic regression model were used to assess the association between risk factors and premenstrual syndrome.Result: The chi-square for trend test showed odds ratios for premenstrual syndrome of 1.72 (95%CI=0.84-3.57), 3.96 (95%CI=1.62-9.80), and 9.78 (95%CI=3.53-27.94) among normal, overweight and obese students, respectively. There were odds ratios of 1.08 (95%CI=0,63-1,86) and 2.66 (95% CI=1,24-5,76) in middle adult women and older adult women, respectively. Contraceptive usage and stress level were also identified as significant factors of premenstrual syndrome. Logistic model using age, contraceptive usage and stress levelmade the best model in showing significant relationships between BMI and stress level and premenstrualsyndrome.Conclusion: There was a significant relationship between body mass index and premenstrual syndrome, and obesity is a risk factor of premenstrual syndrome.Keywords: obesity, body mass index, premenstrual syndrome